Cycle road racing - Newman, Tom (The Crowood Press Ltd, 2013)
Suitable for those entering into cycle road racing, and those improving their performance, this title covers the advanced developments in racing and cycle technology, and guides the readers through all stages of racing, from setting up the bike correctly to race day itself